Labour supply effects of early retirement provision - Ola Lotherington Vestad (Statistics Norway, Research Department, 2012)
The main objective of this paper is to estimate labour supply effects of an early retirement programme in Norway. Detailed administrative data are employed in order to characterize full paths towards retirement and account for substitution from other exit routes, such as unemployment and disability insurance. By exploiting a reduction in the lower age limit for early retirement as a source of exogenous variation in individual eligibility I obtain robust difference-in-differences and triple differences estimates indicating that more than two out of three pensioners would still be working at the age of 63 had the age limit been 64 rather than 62. Hence, although successful in creating a more dignified exit route for early leavers, the programme also generated substantial costs in terms of inducing others to retire earlier.
Keywords: H55; I38; J26; 330; Induced retirement; Pension reform; Matched employer-employee register data; Difference-in-differences.